2018
DOI: 10.1158/0008-5472.can-17-0469
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Enhance Polyfunctionality of Adoptively Transferred T Cells That Target Cytomegalovirus in Glioblastoma

Abstract: Median survival for glioblastoma (GBM) remains <15 months. Human cytomegalovirus (CMV) antigens have been identified in GBM but not normal brain, providing an unparalleled opportunity to subvert CMV antigens as tumor-specific immunotherapy targets. A recent trial in recurrent GBM patients demonstrated the potential clinical benefit of adoptive T-cell therapy (ATCT) of CMV phosphoprotein 65 (pp65)-specific T cells. However, ex vivo analyses from this study found no change in the capacity of CMV pp65-specific T … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 14 publications
1
55
0
1
Order By: Relevance
“…Interestingly, HCMV proteins and nucleic acids have been identified in up to 90% of GBM specimens (6)(7)(8)(9)(10) as well as in some other cancers (11,12). Accumulating clinical data support the relevance of HCMV in GBM (13)(14)(15)(16)(17)(18)(19), with some encouraging responses reported with HCMV-targeted immunotherapies (14)(15)(16)(17)(18). Vaccination with DCs pulsed with tumor lysates led to expansion of mostly anti-CMV T cells in 1 responder (14), and CMV pp65 mRNApulsed autologous DCs showed promising long-term survival data in GBM (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, HCMV proteins and nucleic acids have been identified in up to 90% of GBM specimens (6)(7)(8)(9)(10) as well as in some other cancers (11,12). Accumulating clinical data support the relevance of HCMV in GBM (13)(14)(15)(16)(17)(18)(19), with some encouraging responses reported with HCMV-targeted immunotherapies (14)(15)(16)(17)(18). Vaccination with DCs pulsed with tumor lysates led to expansion of mostly anti-CMV T cells in 1 responder (14), and CMV pp65 mRNApulsed autologous DCs showed promising long-term survival data in GBM (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…58 In a pilot study, 22 patients were randomized to receive adoptive transfer of pp65 specific T cells with CMV DC vaccine or saline. The patients who received the T cells and DC vaccine had a significant increase in CMV specific CD8 T cells that were positive for IFNγ, TNFα and CCL3 compared to patients who received the T cells and saline.…”
Section: As Immunotherapeutic Targetmentioning
confidence: 99%
“…The authors reported that patients given tetanus/diphtheria toxoid had enhanced DC migration, and significantly improved progression‐free and overall survival that exceeded 40 months (ClinicalTrials.gov identifier: NCT00639639) . Another recent clinical study showed that patients with GBM who received anti‐CMV adoptive cell transfer exhibited even better cellular immune responses further to an improved survival pattern following vaccination with a CMVpp65 RNA‐pulsed DC vaccine candidate . Prolonged treatment with valganciclovir as an adjunct to standard therapy has been shown to benefit patients with newly diagnosed or recurrent GBM, although randomized trials are warranted in the future .…”
Section: Cmv‐specific Memory Inflation Shapes Global and Anti‐tumourmentioning
confidence: 99%
“…124 Another recent clinical study showed that patients with GBM who received anti-CMV adoptive cell transfer exhibited even better cellular immune responses further to an improved survival pattern following vaccination with a CMVpp65 RNA-pulsed DC vaccine candidate. 125 Prolonged treatment with valganciclovir as an adjunct to standard therapy has been shown to benefit patients with newly diagnosed or recurrent GBM, although randomized trials are warranted in the future. [126][127][128] It is, however, worthwhile to examine in future studies whether antiviral therapy may also benefit patients with GBM through additional immune-related pathways, based on the clinical case of a patient with ependymoma, who after ganciclovir treatment showed enhanced innate immune and T-cell activation.…”
Section: Glioblastoma Multiformementioning
confidence: 99%